Faktor Penyebab Ketidaklengkapan Pengisian Berkas Rekam Medis Pasien Rawat Inap - Angga Kristiana Putri; Ida Nurmawati; Maya Weka Santi; Selvia Juwita Swari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Incomplete medical records have an impact on the low quality of medical records and health services. The purpose of this study is to analyze the factors that cause incomplete filling in medical record files for inpatients at the hospital based on the 5M elements of management (Man, Money, Methods, Machine, Material). This study was a literature review. The results of the analysis showed that incomplete medical record files were 34.3%. Many of the items that were not filled in completely from the medical record form included authentication from doctors and nurses, namely 7 articles. Factors causing incomplete filling of inpatient medical record files with the highest percentage were lack of knowledge of staff, lack of budget, lack of rewards and punishments, non-specific or incomplete checklists for assessing file completeness, and medical record files that were less systematic. Efforts that need to be made are increasing the knowledge of officers about the importance of completing medical record files, implementing a reward and punishment system to motivate officers, improving checklist sheets and medical record files according to standards.Keywords: incompleteness; filling; inpatient medical record ABSTRAK Ketidaklengkapan rekam medis berdampak pada rendahnya mutu kualitas rekam medis dan pelayanan kesehatan. Tujuan dari studi ini adalah untuk menganalisis faktor penyebab ketidaklengkapan pengisian berkas rekam medis pasien rawat inap di rumah sakit berdasarkan unsur manajemen 5M (Man, Money, Methods, Machine, Material). Studi ini merupakan literature review. Hasil analisis menunjukkan bahwa ketidaklengkapan berkas rekam medis adalah 34,3%. Item yang banyak tidak terisi secara lengkap dari formulir rekam medis di antaranya adalah autentifikasi dari dokter maupun perawat yaitu sebanyak 7 artikel. Faktor penyebab ketidaklengkapan pengisian berkas rekam medis rawat inap dengan persentase tertinggi adalah kurangnya pengetahuan petugas, kurangnya anggaran, belum adanya reward dan punishment, checklis penilaian kelengkapan berkas yang tidak spesifik atau tidak lengkap, dan berkas rekam medis yang kurang sistematis. Upaya yang perlu dilakukan adalah meningkatkan pengetahuan petugas tentang pentingnya kelengkapan berkas rekam medis, menerapkan sistem reward dan punishment untuk motivasi petugas, memperbaiki lembar checklist dan berkas rekam medis sesuai standar.  Kata kunci: ketidaklengkapan; pengisian; rekam medis rawat inap